Analysis of Transmission Characteristic of Straight Bevel Gear and Zero Spiral Bevel Gear - Li Duo; Hu Yumei (Jixie chuandong)
The finite element model of a pair of straight bevel gears is established,and the simulation is carried out by using the ANSYS/LS-DYNA software to verify the accuracy of the simulation method. Based on this,a pair of zero spiral bevel gears are created for comparative analysis. According to the simulation results,the gear contact force,tooth surface contact stress,tooth root bending stress and vibration of large gear are compared and analyzed. It is found that the transmission characteristics of the straight bevel gear and the zero spiral bevel gear are obvious difference at the same load and speed. This provides a reference for the selection and application of these two types of bevel gears in the aeronautical field.